Konstruksi Sosok Anies Baswedan dalam Pemberitaan Pembongkaran Bambu Getah Getih di Media Online Tempo.Co - Dini Yuliani Rahmah; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
Governor of DKI Jakarta Anies Baswedan has been critized by many people regarding his decision to dismantle bambu getah getih instalations which spent Rp 550 million. This research using contructivist paradigm with qualitative approach and social semiotic analysis M.A.K Halliday through three analytical tools including field of discourse, tenor of discourse, and mode of discourse. This research found in field of discourse Tempo.co show that bambu getah getih phenomenon is the way to construct Anies Baswedan’s figure, in tenor of discourse Tempo.co using public official, political party, artist and citizen that has pro and contra with Anies Baswedan figure, meanwhile in mode of discourse Tempo.co using tendentious words for Anies Baswedan’s figure. From this research, researches also found that Anies Baswedan figure constructed as an incompetent leader, as an arrogant leader, as a cunning leader, as conquerer leader, as a has no policy leader and as has no direction in order reign.